2017
DOI: 10.1161/jaha.116.004971
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Hydrogen Sulfide Enhances Carotid Sinus Baroreceptor Sensitivity by Activating the Transient Receptor Potential Cation Channel Subfamily V Member 1 (TRPV1) Channel

Abstract: BackgroundWe aimed to investigate the regulatory effects of hydrogen sulfide (H2S) on carotid sinus baroreceptor sensitivity and its mechanisms.Methods and ResultsMale Wistar‐Kyoto rats and spontaneously hypertensive rats (SHRs) were used in the experiment and were given an H2S donor or a cystathionine‐β‐synthase inhibitor, hydroxylamine, for 8 weeks. Systolic blood pressure and the cystathionine‐β‐synthase/H2S pathway in carotid sinus were detected. Carotid sinus baroreceptor sensitivity and the functional cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…We also observed a depletion of Eubacteriaceae and Peptococcaceae in the order of Clostridiales and in the phyla of Firmicutes, in our b1.b2 Adr KO mice. These strains are largely considered to be beneficial, with Peptococcaceae a sulfate-reducing bacteria (Petzsch et al, 2015 ), a property suggested to be important in regulation of BP (Ahmad et al, 2012 ; Yu et al, 2017 ). Similarly, we saw a reduction in Bilophila in the b1.b2 Adr KO mice, which are, however considered to be largely pathogenic, which may be related to reduced presence of hydrogen sulfide (da Silva et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a depletion of Eubacteriaceae and Peptococcaceae in the order of Clostridiales and in the phyla of Firmicutes, in our b1.b2 Adr KO mice. These strains are largely considered to be beneficial, with Peptococcaceae a sulfate-reducing bacteria (Petzsch et al, 2015 ), a property suggested to be important in regulation of BP (Ahmad et al, 2012 ; Yu et al, 2017 ). Similarly, we saw a reduction in Bilophila in the b1.b2 Adr KO mice, which are, however considered to be largely pathogenic, which may be related to reduced presence of hydrogen sulfide (da Silva et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al found that H 2 S could increase intracellular cGMP level via sulfhydrate phosphodiesterase 5A to inhibit the cGMP degradation ( Sun et al, 2017 ). Moreover, Yu et al (2017) demonstrated that S -sulfhydration of TRPV1 by CBS-derived H 2 S in carotid sinus facilitated carotid sinus baroreceptor sensitivity to participated the control of blood pressure.…”
Section: Sulfhydration Mediates H 2 S-induced Biolmentioning
confidence: 99%
“…In recent years, it has been suggested that the arterial baroreceptor reflex participates in the long-term regulation of blood pressure [34,35], and pressure-dependent discharges from the carotid sinus nerve are significantly reduced in correlation with a decrease in TRPV1 protein expression in baroreceptors from spontaneously-hypertensive rats [36]. In addition, symptoms of high blood pressure and a marked decline in aortic nerve activity have been found in ASIC2-knockout mice [3].…”
Section: Discussionmentioning
confidence: 99%